This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: oldhomewk 37 PAPAGEORGE, MATT Due: Apr 28 2008, 4:00 am 1 Question 1, chap 18, sect 3. part 1 of 1 10 points In testing a new material for shielding spacecraft, 149 small ball bearings, each mov- ing at a supersonic speed of 415.7 m/s, collide head-on and elastically with the material dur- ing a 0.590 min interval. If the bearings each have a mass of 8.6 g and the area of the tested material is 0.74 m 2 , what pressure is exerted on the material? Correct answer: 40 . 6687 Pa (tolerance 1 %). Explanation: Basic Concepts: P = F A Conservation of momentum: p = F t Elastic collision: v f =- v i Given: t = 0 . 590 min N = 149 m = 8 . 6 g v = 415 . 7 m / s A = 0 . 74 m 2 Solution: p = mv f- mv i = m (- v i )- mv i =- 2 mv i and F = p t For one bearing, P = vextendsingle vextendsingle vextendsingle p t vextendsingle vextendsingle vextendsingle A = 2 mv A t For all of the bearings, P = N parenleftbigg 2 mv A t parenrightbigg = 2(149)(8 . 6 g)(415 . 7 m / s) (0 . 74 m 2 )(0 . 59 min) parenleftbigg 1 min 60 s parenrightbigg parenleftbigg 1 kg 1000 g parenrightbigg = 40 . 6687 Pa Question 2, chap 18, sect 4. part 1 of 2 10 points A simple U-tube that is open at both ends is partially filled with a liquid of density 614 kg / m 3 . Water is then poured into one arm of the tube, forming a column 15 cm in height, as shown in the following diagram. The density of heavy liquid is 1000 kg / m 3 . h 1 15 cm light liquid 614 kg / m 3 heavy liquid 1000 kg / m 3 What is the difference, h 1 , in the heights of the two liquid surfaces? Correct answer: 9 . 42997 cm (tolerance 1 %). Explanation: Basic Concepts: gauge pressure, varia- tion of pressure with depth Because the liquid in the U-tube is static, the pressure exerted by the heavy liquid column of height in the right branch of the tube must balance the pressure exerted by the liquid of height h 1 + in the left branch. Therefore, P + ( + h 1 ) g = P + h g . oldhomewk 37 PAPAGEORGE, MATT Due: Apr 28 2008, 4:00 am...
View Full Document
- Spring '09